2019
DOI: 10.3390/ijms20051117
|View full text |Cite
|
Sign up to set email alerts
|

mTOR is a Key Protein Involved in the Metabolic Effects of Simple Sugars

Abstract: One of the most important threats to global human health is the increasing incidences of metabolic pathologies (including obesity, type 2 diabetes and non-alcoholic fatty liver disease), which is paralleled by increasing consumptions of hypercaloric diets enriched in simple sugars. The challenge is to identify the metabolic pathways affected by the excessive consumption of these dietary components when they are consumed in excess, to unravel the molecular mechanisms leading to metabolic pathologies and identif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
34
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(37 citation statements)
references
References 56 publications
1
34
0
2
Order By: Relevance
“…Sangüesa Puigventós et al. (2019) also showed that fructose feeding for two months increases the phosphorylation of hepatic mTORC1 and phosphorylated levels of ULK‐1 (Sanguesa Puigventós et al., 2019). Ward et al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sangüesa Puigventós et al. (2019) also showed that fructose feeding for two months increases the phosphorylation of hepatic mTORC1 and phosphorylated levels of ULK‐1 (Sanguesa Puigventós et al., 2019). Ward et al.…”
Section: Discussionmentioning
confidence: 99%
“…Sanguesa Puigventós et al. (2019) reported that mTORC1 may attenuate lipid catabolism by inhibiting fatty acid β‐oxidation (Sanguesa Puigventós et al., 2019). Therefore, the inhibition of autophagy leads to increase glycolysis and fat accumulation along with high inflammatory response in liver.…”
Section: Discussionmentioning
confidence: 99%
“…However, while the mTORC1 contains the regulatory-associated protein of mTOR (Raptor) and the inhibitory subunit proline-rich Akt substrate of 40kDa (PRAS40), the mTORC2 exhibit the rapamycin-insensitive companion of mTOR (Rictor) and the regulatory proteins Protor1/2 and mSin1. These structural particularities of mTORC1 and mTORC2 are responsible for a different response pattern to a wide variety of upstream signals, as well as for activating different downstream effectors, thus resulting in well differentiated cellular responses [10][11][12]. mTORC1 and mTORC2 respond to insulin and related growth factors through the interconnected MAPK/ERK and PI3K/AKT/mTOR signaling pathways [13,14].…”
Section: The Mtor Signaling Pathwaymentioning
confidence: 99%
“…In addition, AMPK activation inhibits the mTORC1 activation and ER stress response [8]. Recent studies have also indicated that alteration of AMPK/mTOR pathway activity is involved in steatosis, insulin resistance, and modulation of lipid metabolism in HFD induced mice by stimulation of autophagy [10,11]. Thus, the inhibition of hepatic dyslipidemia via AMPK activation is considered as a viable therapeutic strategy in prevention of occurrence and development of NAFLD [12].…”
Section: Introductionmentioning
confidence: 99%